2022
DOI: 10.14426/cristal.v10i2.571
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising ‘caring’ in e-tutor-student interactions during the Covid-19 pandemic in an ODeL university in South Africa

Abstract: In South Africa and elsewhere, the outbreak of Covid-19 in 2020 and the lockdown regulations forced both academics and students to adapt to a new reality of fully online modules and assessments. This catapulted relations in higher education into the spotlight. The concern of this paper is how e-tutors in an Open Distance e-Learning (ODeL) university in South Africa have enacted care in online interaction with the students during this period. Available research focuses on online interaction; however, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…At the ODeL university where the current study was conducted, planned and well-placed student support endeavours existed before the pandemic, constituting an element of care for the students involved. Of particular importance was stopping the posting of learning materials to the students involved, accompanied by moving all forms of teaching, learning, and assessment to a fully online medium (Shange, 2022). During this time, I observed that online student engagement remained a concern in the English module where this research was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…At the ODeL university where the current study was conducted, planned and well-placed student support endeavours existed before the pandemic, constituting an element of care for the students involved. Of particular importance was stopping the posting of learning materials to the students involved, accompanied by moving all forms of teaching, learning, and assessment to a fully online medium (Shange, 2022). During this time, I observed that online student engagement remained a concern in the English module where this research was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…One such approach is online tutoring, or e-tutoring, which has become more prevalent as higher education institutions (HEIs) transition to online learning modes (Okoro et al, 2021). Unisa, as the largest distance-learning institution in Africa, has long embraced and facilitated online tutoring to advance knowledge and human capital (Shange, 2022). This aligns with South Africa's national development strategy, Vision 2030, which aims to eradicate poverty, reduce inequality, and address unemployment (Blom, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So, tell us why your research is important in your specific context, give us an explanation of why the topic is relevant in the particular context and in the broader literature; let us know whether and how the paper is uniquely local/African/South African. As an example, while both Feldman(2020) andShange (2022) employ the notion of care, how care plays out during the pandemic at Stellenbosch University and at UNISA, the largest open and distance education institution in South Africa, differs widely.…”
mentioning
confidence: 99%